Design, synthesis and biological evaluation of a series of novel GPR40 agonists containing nitrogen heterocyclic rings. Issue 18 (1st October 2018) - Sun, Zhaozhu; Zhou, Tian; Pan, Xuan; Yang, Ying; Huan, Yi; Xiao, Zhiyan; Shen, Zhufang; Liu, Zhanzhu
Graphical abstract: Highlights: A series of novel GPR 40 agonists was prepared. The compounds feature the nitrogen-containing heterocycles. Compound 30 exhibited efficacy both in vitro and in vivo . Abstract: A novel series of GPR40 agonists is designed by introducing nitrogen-containing heterocyclic ring at the terminal phenyl ring of TAK-875 with the aim of decreasing its lipophilicity. Three different β-substituted phenylpropionic acids were investigated as the acidic components. A total of 34 compounds have been synthesized, among which, compound30 exhibited comparable GPR40 agonistic activity in vitro with TAK-875 and relatively lower lipophilicity through calculation (30, EC50  = 1.2 μM, cLogP = 1.3; TAK-875: EC50  = 5.1 μM, cLogP = 3.4). Moreover, compound30 was able to enhance the insulin secretion of primary islets isolated from normal ICR mice and showed no obvious inhibition against cytochromes P450 in vitro . In vivo, compound30 exhibited efficacy in oral glucose tolerance test (oGTT) in normal ICR mice.